Ausgewählte Probleme der Variationsrechnung: 21.6. bis 26.6.1970 - Heinz, Erhard; Hildebrandt, Stefan; Jäger, Willi (Tagungsbericht, 1970)
H. W. Alt, Göttingen; R. Böhme, Göttingen; H. F. Böttger, Mainz; R. Courant, New York; J. Frehse, Frankfurt; C. Gerhardt, Mainz; E. Giusti, Pisa; G. Goldhorn, Mainz; F. P. Harth, Mainz; Haverkamp, Münster; E. Heinz, Göttingen; S. Hildebrandt, Mainz; E. Hölder, Mainz; W. Jäger, Göttingen; H. Kaul, Mainz; M. Miranda, Ferrara; J. C. C. Nitsche, Minneapolis; C. Schäfer, Mainz; B. Schmidt, Mainz; R. Schneider, Frankfurt; U. Staude, Mainz; K. Steffen, Mainz; F. Tomi, Göttingen; W. von Wahl, Göttingen; H. Werner, Münster; K. O. Widman, Uppsala
Beitr. teilw. dt., teilw. engl
Keywords: Konferenzschrift